(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the pH and total soluble solids (TSS) content of whey protein beverages. Nine products of three different flavors (vanilla, strawberry and chocolate) of the following brands Muke®, Best Whey®, and Essencial Nutrition Whey®, had their pH evaluated by potentiometry, and their TSS evaluated by refractometry. The lowest pH recorded was for Muke® Chocolate (5.75), and the highest was for Essencial Nutrition Whey® Cacao (6.91). Regarding TSS, the lowest average was for Essencial Nutrition Whey® Vanilla (10.17), and the highest was for Essencial Nutrition Whey® Red Berry (16.66). There was no statistically significant difference in pH and TSS among the flavors and brands evaluated. It was concluded that the analyzed beverages had a higher pH than the pH that is critical to dental enamel and the TSS content was considered high.